The relationship experiences of professional nurses with nurse managers - Sindiwe Valencia James; Wilhelmina J Kotzé; Dalena van Rooyen (AOSIS, 2005)
This qualitative study was undertaken to explore and describe the experiences of professional nurses in their relationships with nurse managers. Opsomming Hierdie kwalitatiewe studie is onderneem om die belewenisse van professionele verpleegkundiges ten opsigte van hulle verhoudings met verpleegbestuurders te verken en te beskryf. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.